2010
DOI: 10.1007/s00595-009-4092-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgery in the treatment of neuroblastoma

Abstract: The role of surgery varies greatly according to the clinical condition of the patients with neuroblastoma. A surgical resection is the mainstay of treatment for a localized tumor. However, in the era of intense chemotherapy associated with hematopoietic stem cell plant rescue, surgical resections are recommended without sacrificing the kidney or major vessels. Tumor biology further defines the necessity of supportive chemotherapy or radiation after surgical resection. The presence of diverse terminology concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 33 publications
0
19
0
2
Order By: Relevance
“…On the other hand, Castel et al [20] found that delayed surgery after chemotherapy contributes to the good control of stage IV disease, although the final outcome of these patients was determined more by metastatic relapses than by the degree of resection. Kaneko et al and Kubota et al reported that systemic extensive surgery for advanced or metastatic neuroblastoma is no longer required if therapy supplemented with intensive pre-and postoperative chemotherapy is given [4,21]. In the present study, the clinical stage and tumor biology of advanced neuroblastoma in patients aged 12 months or older was associated with the overall survival rate.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…On the other hand, Castel et al [20] found that delayed surgery after chemotherapy contributes to the good control of stage IV disease, although the final outcome of these patients was determined more by metastatic relapses than by the degree of resection. Kaneko et al and Kubota et al reported that systemic extensive surgery for advanced or metastatic neuroblastoma is no longer required if therapy supplemented with intensive pre-and postoperative chemotherapy is given [4,21]. In the present study, the clinical stage and tumor biology of advanced neuroblastoma in patients aged 12 months or older was associated with the overall survival rate.…”
Section: Discussionmentioning
confidence: 46%
“…There are three types of surgical intervention for neuroblastoma: initial tumor extirpation, biopsy of the tumor at initial diagnosis; and radical surgery as a second-look operation after biopsy and induction chemotherapy. The role of surgical resection in the treatment of neuroblastomas is still controversial [4]. We conducted the present study to evaluate the implications of surgical intervention for neuroblastomas in patients under 12 months of age versus those over 12 months of age, based on an analysis of patients treated at one institution.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the overall survival of children with NB who underwent radioguided surgery was 83.3% in reasonably long鈥恡erm follow up (median follow up, 57 months). The role of intensive surgery for advanced NB has remained controversial and it is less likely that the type of surgery contributes to improving patient survival; however, it should be noted that there were no significant postoperative complications in our patients. Some previous reports, including ours, described that over 30% of children with high鈥恟isk NB were experiencing at least one complication postoperatively, such as renovascular problems, resection of normal organs, and postoperative hemorrhage .…”
Section: Discussionmentioning
confidence: 66%
“…The risk of relapse is found to be higher in patients with MYCN amplification or unfavorable histology. Supportive treatment seems to be necessary in 10% of Stage 1 patients and in 20% of Stage 2 patients with risk factors [12].…”
Section: Discussionmentioning
confidence: 99%